"It's the Challenger, Stupid!": Elections and the Theory of Rank-Order Tournaments - Michael Funk; Reiner Eichenberger (Center for Research in Economics, Management and the Arts (CREMA), 2007)
Democratic elections look very much like a contest where voters have to compare the candidates according to an ordinal ranking. Nevertheless, the theory of tournaments has not yet been applied to Political Economics. Therefore, we deploy tournament models to analyse elections. The main difference between tournaments in a firm and election tournaments is a systematic asymmetry between the contestants: whereas the voters have plenty of information about the incumbent, they hardly know anything about the challenger. Unlike most models of political accountability that model the challenger as a standard, we focus on the specific role of the challenger and model him as a random draw with a given expected ability. Consequently the ordinal ranking of the candidates contains plenty of noise, which weakens the incumbent's incentives to exert e exteuroort. After the presentation of the basic model, several extensions of the tournament theme in politics are explored. The model gives a fresh insight into very important aspects of politics, such as sabotage and selection, and it identifies exective policy reforms, e.g. the deregulation of politics.
Keywords: D8; D72; H11; 330; Tournament; Political Agency; Elections